Levels of molecular angiogenic and antiangiogenic in pregnant women with risk of preeclampsia - Wulandari, Diah; Sulchan, Mohamad; Hidayat, Syarief Thaufik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Angiogenic and antiangiogenic imbalances play a major role in the pathogenesis of preeclampsia. Increased production of sFlt-1 by the placenta causes free circulating PIGF and VEGF concentrations to lower because it is bound by sFlt-1. Measuring levels of angiogenic and antiangiogenic proteins as biomarkers indicates placental dysfunction and distinguishes preeclampsia from other disorders. This study aims to analyze the levels of angiogenic and antiangiogenic molecules in pregnant women at risk for preeclampsia. Methods: The study with a cross-sectional design was carried out in 11-15 weeks gestational age whom had a risk of preeclampsia with 30 samples in primary health care starting April-August 2018. Blood serum was measured by molecular levels of VEGF, PlGF, sFlt-1, and sFlt-1/PlGF ratio using the ELISA method. Data analysis used Pearson product moment test. Results: The mean of VEGF levels are 15.5±21.6, PlGF 89.7±55.5, sFlt-1 11519.4±5126.0 and the ratio sFlt-1/PlGF 166.7±102.1. Correlation value of risk factors for preeclampsia with molecular levels of VEGF r= -0.05; p = 0.76, PlGF r= -0.21; p = 0.26, sFlt r= 0.01; p =0.99 and ratio sFlt-1/PlGF r = 0.10; p = 0.58. Conclusions: The higher the total score of preeclampsia risk factor, the lower the molecular level of VEGF and PlGF is. Moreover, the higher the total score of preeclampsia risk factor, the higher the molecular level sFlt-1 and the sFlt-1/PlGF ratio is. There are no significant correlation between total score of preeclampsia risk factor and levels of molecule VEGF, PlGF, sFlt-1 and sFlt-1/PlGF ratio.